The Power Dynamic through Language in the March Family in Little Women Movie - KM., Nurastriani Saputri; Bahar, Bahar (British (Jurnal Bahasa dan Sastra Inggris), 2025)
Little Women is a film that offers strong and well-defined characters who each have their own unique way of speaking. Through the analysis of their language, we can see how their strengths, weaknesses, and internal conflicts are reflected in the way they use language. This study aims to reveal the strengths through language found in the March family in the film Little Women. In this study, the researcher used a qualitative descriptive research method using the analysis of the theory of French and Raven (1959). Data collection techniques were carried out by means of observation and literature study. Based on the research that has been done, the researcher draws the conclusion that Jo March eventually succeeded in becoming a writer and her books were successfully published. In this study, the author found four powers contained in Frenc and Raven's theory, namely Legitimate Power, Reward Power, Coercive Power, and information power.